Smart contracts: the new method of interaction between the law and technology - Jesus Manuel Niebla Zatarain; Paola Jackeline Ontiveros Vázquez (International Journal of Digital Law)
Technology has reshaped the law. The Internet and derived technologies have led to the adaptation of traditional legal figures with the objective of bringing certainty to users and developers. A field that has been subject of constant technological development is contact law. This paper will address this scenario from the perspective of smart contracts, which allows not only a digital representation of the obligations agreed by the parties, but also the capacity to solve discrepancies to ensure operation. Finally, this joint approach offers compatibility with transactions that take place in digital scenarios, contributing to a safer and law compliant cyberspace.